ENHANCING THE INVESTMENT PROMOTION AND FACILITATION FRAMEWORK IN UZBEKISTAN (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This study examines the current state of Uzbekistan’s investment promotion and facilitation framework and identifies key measures necessary to strengthen its institutional effectiveness. In recent years, Uzbekistan has pursued extensive reforms aimed at improving the business environment, increasing transparency, and attracting higher volumes of foreign direct investment. Despite notable progress such as the establishment of specialized institutions, expansion of digital public services, and development of regional investment assessment tools structural and institutional challenges continue to hinder the full realisation of the country’s investment potential. The analysis highlights persistent issues related to overlapping mandates, weak coordination between core government bodies, limited policy advocacy capacities, and insufficient monitoring and evaluation mechanisms. Special attention is given to the role of the Investment Promotion Agency (UzIPA) and the Ministry of Investments, Industry and Trade (MIIT), whose functions remain fragmented and poorly integrated into national strategic planning. The study argues that strengthening institutional clarity, introducing modern CRM-based investor servicing tools, enhancing aftercare systems, and ensuring evidence-based decision-making are essential steps for building a more coherent and competitive investment climate. The findings contribute to ongoing policy debates and offer practical recommendations to support Uzbekistan’s transition toward a more efficient, investor-oriented governance framework.
Keywords: Investment, investment climate, foreign direct investment, GDP, investment promotion, special economic zone, local investors.